Simulation and experimental validation of damping characteristic for a valve-controlled adjustable shock absorber. Issue 2 (2018) - Deng, Min; Hua, Yanqiu; Wu, Guangqiang
In this study, a novel valve-controlled adjustable shock absorber is presented along with its working principle and valve system behaviour. According to the theory of hydraulics and elasticity, the physical parametric model for the shock absorber force characteristics was established then simulated in MATLAB software environment. The simulation results are compared with the shock absorber bench test at different control currents under the QC/T545 test standard to demonstrate the proposed model's validity. On the basis of the proposed and validated shock absorber model, the influence of the solenoid valve proportion orifice radius on damping characteristics was analysed and summarised to potentially offer reference for the future studies.